Ahli Waris ‘Ashabah Perspektif Hukum Keluarga Islam - Arofik, Slamet; Fidaroini, Rafida (ADIDAS: Asosiasi Dosen Syari'ah STAI Darussalam Nganjuk, 2021)
Among the heirs who get the inheritance of the deceased are the heirs of 'ashabah. These heirs are